Adventitious isolation of a pseudorotaxane complex of a trans-bis(Hydroxymethylbenzo)-27-crown-9 pyridyl cryptand and a viologen. Issue 8 (2nd August 2020) - Pederson, Adam M.-P.; Gibson, Harry W.; Slebodnick, Carla
ABSTRACT: The adventitious isolation and crystal structure of a pseudorotaxane complex of a trans -substituted dibenzo-27-crown-9-based pyridyl cryptand (6 ) and N, N'-dimethyl-4, 4ʹ-bipyridinium bis(hexafluorophosphate) (5 ) are reported. Graphical abstract: